(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article is devoted to the peculiarities of the development of the content of technical and technological training in maritime educational institutions of Ukraine at the end of the 40s. XX – at the beginning of the XXI century. The relevance of the article theme is related to the fact that further automation and digitalization of the maritime industry will not reduce manpower demand, but the requirements for the skills of maritime specialists will change. The author notes maritime educational institutions should transform approaches to training specialists for the shipping industry in accordance with new technological challenges. In the article the author analysis and compares curriculums of different historical periods. During the analysis, it was found in the post-war period the content of technical and technological training for various areas of the ship-engineering specialty was almost identical. It is explained by the fact that in the conditions of fleet heterogeneity and a critical shortage of specialists, the country’s leadership set the task for maritime educational institutions as soon as possible to provide the shipping industry with personnel capable of performing universal professional tasks. At the beginning of the 60s of the XX century with the development of ship power systems, the approaches to the organization of training of ship engineers are changing too. During this period, maritime educational institutions move from the concept of differentiation of the profession of ship engineer to its integration into a single area of training “Ship power systems”. A new round in the development of technical and technological training of ship engineers is due to the intensification of the processes of informatization and globalization of all spheres of human activity, including the maritime industry, at the beginning of the 21st century. The results of the presented study provide grounds for concluding the increasing pace of technological progress requires the maritime education system flexibility and the ability to predict prospective innovations in the technical support of the shipping industry. It is relevant to revise approaches to the development of curricula in modern maritime educational institutions with the possibility of supplementing it with optional courses.